PROMOTING SOCIAL WORK GRADUATES’ EMPLOYMENT THROUGH THE SOCIAL WORK CURRICULUM: EMPLOYERS’ PERSPECTIVES ON THE EMPLOYABILITY OF UNISA’S NEWLY QUALIFIED SOCIAL WORKERS - Alpaslan, Assim (Social Work/Maatskaplike Werk, 2019)
<span style="font-family: 'Times New Roman','serif'; font-size: 14pt; mso-bidi-font-size: 12.0pt; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB">The silence about employers’ perspectives on the employability of newly qualified Social Work graduates from the largest open distance-learning university in South Africa was highlighted as the problem for this study. Underpinned by the theory of collaborative advantage as the theoretical framework adopted for this study, and following a qualitative research approach, the researcher entered into a research partnership with the social work fraternity. The aim was to explore employers’ perspectives on the employability of Unisa’s newly-qualified social workers and to gather suggestions for promoting graduates’ employment, and accordingly informing Unisa’s social work curriculum. This paper reports on these perspectives and suggestions.